2019
DOI: 10.1007/s00423-018-1744-4
|View full text |Cite
|
Sign up to set email alerts
|

Stringent fluid management might help to prevent postoperative ileus after loop ileostomy closure

Abstract: Purpose The present study aimed to analyze the impact of perioperative fluid management on postoperative ileus (POI) after loop ileostomy closure. Methods Consecutive loop ileostomy closures over a 6-year period (May 2011-May 2017) were included. Main outcomes were POI, defined as time to first stool beyond POD 3, and postoperative complications of any grade. Critical fluid managementrelated thresholds including postoperative weight gain were identified through receiver operator characteristics (ROC) analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
6
15
1
Order By: Relevance
“…In a recent systematic review and meta-analysis conducted by Richard Garfinkle(4), the pooled estimate of POI was 8% (range from 6.7% to 12.4% varied by definition). The incidence of POI in our study is 9.7%, which is in accordance with Richard's study and many previous series (25,26). Aside from lengthen time of stay, delayed recovery of gastrointestinal function is related with increased healthcare costs and risk for other morbidities (27).…”
Section: Discussionsupporting
confidence: 92%
“…In a recent systematic review and meta-analysis conducted by Richard Garfinkle(4), the pooled estimate of POI was 8% (range from 6.7% to 12.4% varied by definition). The incidence of POI in our study is 9.7%, which is in accordance with Richard's study and many previous series (25,26). Aside from lengthen time of stay, delayed recovery of gastrointestinal function is related with increased healthcare costs and risk for other morbidities (27).…”
Section: Discussionsupporting
confidence: 92%
“…Our group previously studied effects of fluid balance on postoperative outcomes after ileostomy takedown. Both excess fluids and weight gain were found to be independent predictors of postoperative ileus and emphasize the importance of stringent fluid management [6].…”
Section: Discussionmentioning
confidence: 84%
“…Fluid management standards in patients undergoing major surgery have changed in the last years. Several studies revealed a direct relationship between perioperative fluid balance and postoperative adverse events [1][2][3][4][5][6]. Enhanced…”
Section: Introductionmentioning
confidence: 99%
“…Morbidity was graded based on severity of complications as suggested and validated by Dindo et al [13]. Majority of the earlier studies showed goal-directed fluid management improves the patient's outcome (reduces postoperative complications, lactate level, length of hospital stay, ICU stay, days to oral intake, day of return of bowel movement, and mortality) [2225, 29]. There was no difference between the three groups with respect to development of MODS or survival.…”
Section: Discussionmentioning
confidence: 99%